Towards a Common Aim and Framework for Tools and Research in Support of Bible Translation and Biblical Language Online Learning - O'Rear, Paul A. (HIPHIL Novum, 2019)
The broader biblical studies and scholarly community has had a burgeoning interest in developing tools and resources that are useful not only for itself, but also in support of related ministry related activities, such as Bible translation and the teaching and equipping of pastors in the Majority world context. This has led to the formation of groups such as the Global Education and Research Technologies (GERT) section of the Society of Biblical Literature (SBL), as well as activities and projects on such sites as http://biblicalhumanities.org and https://github.com/biblicalhumanities. While these groups have been valuable for productive interaction, they have not had very clear overarching objectives. Participants offer valuable contributions, but much of the work tends to go on in isolation following the inspiration and motivation of the individuals rather than of the group. This paper identifies this problem, some potential aims, and Bible translation resources from SIL as a sort of case study where tools and directed work from the broader community could benefit both the biblical studies/scholarly community and the Bible translation community at the same time. It also identifies the necessary work of synthesizing the specialized research and data of the scholarly community as part of the overall broader needs of the Bible translation movement. This synthesizing work is a critical notion towards conceiving a framework that would address a suggested aim for our joint communities.